Relationship between sleep variables and interoceptive awareness in daytime workers - Shoichi Asaoka; Ryuichiro Yamamoto; Kenta Nozoe; Ritsuko Nishimura (PLoS ONE, 2025)
Interoception refers to the sensation of internal and physiological bodily states, such as heart rate, and contributes to the maintenance of bodily internal homeostasis. Some studies showed that interoceptive awareness is related to experiencing nightmares and subjective sleep quality. Similarly to the perception of heart rate variability, sleepiness is thought to be mainly evoked by homeostatic processes and is based on the awareness and recognition of internal body signals. However, the relationship between subjective excessive daytime sleepiness and interoceptive awareness has not been addressed. Therefore, this study examined the relationship between interoceptive awareness and multiple sleep variables including subjective excessive sleepiness in daytime workers. A web questionnaire survey was conducted targeting daytime workers in Japan, and data from 461 participants were used for analyses. Multiple regression analyses showed weak but significant relationships between subjective excessive daytime sleepiness, insomnia symptoms, nightmare distress, and dream frequency and the components of interoception awareness measured by the Multidimensional Assessment of Interoceptive Awareness. However, no components of interoceptive awareness were related to workday sleep loss or social jetlag of day workers. The results of this study suggest that subjective sleepiness, in addition to nightmare distress and sleep quality, is associated with interoceptive awareness. To the best of our knowledge, this study is the first to analyze the relationship between subjective daytime excessive sleepiness and interoceptive awareness. Further investigation of this relationship is expected to lead to a better understanding of sleep disorders and to elucidate individual differences in the accuracy of subjective assessments of sleepiness.